2016
DOI: 10.1016/j.applthermaleng.2016.07.163
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of effect of fill ratio and inclination angle on a thermosiphon heat pipe thermal performance

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(16 citation statements)
references
References 26 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The filling ratio is a very main issue to impact the thermal performance of straight heat pipe. Figure (5) shows the variation of measurement average wall of evaporator temperature of input power ranging from 10 W to 100 W at a stage of 10 W when the fill ratios 15%, 25%, 50% and 85%. It can be understood from the figure that the average wall temperature increases with increase input power for each fill ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The filling ratio is a very main issue to impact the thermal performance of straight heat pipe. Figure (5) shows the variation of measurement average wall of evaporator temperature of input power ranging from 10 W to 100 W at a stage of 10 W when the fill ratios 15%, 25%, 50% and 85%. It can be understood from the figure that the average wall temperature increases with increase input power for each fill ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad et al, [5] studied the effect of fill ratio and inclination angle on thermal performance of thermosyphon heat pipe by using a new CFD simulation. The results showed that the best fill ratio and inclination angle were 65% and 90°.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamic Ansys/Fluent 6.2, 13, and 15 have been used by researchers of different studies reported by References [21][22][23][24][25][26] to simulate the wickless heat pipe under different operating parameters, such as input heat flow, filling ratio, inclination angle, and different working fluids (water and R134a). All of these parameters have an effect on the performance of the wickless heat pipe.…”
Section: Introductionmentioning
confidence: 99%
“…There are also several studies aimed to find the optimum filling ratio for different types of thermosiphons [7,8,9]. A team of researchers [10] investigated how the fill ratio and inclination angle is affecting the thermal performance of a thermosiphon. When the evaporator was filled to 65%, the thermal resistance of the gravitational heat pipe recorder the lowest value.…”
Section: Introductionmentioning
confidence: 99%